Modelling of metal extrusion using ABAQUS - Kathirgamanathan, P.; Neitzert, T. (The Proceedings of New Zealand Metals Industry, 2006)
The mechanical properties of processed metal depend greatly on the micro-structural changes during the extrusion process. A clear theoretical concept of the thermodynamics and tribology of the metal extrusion process with respect to the major process parameters, namely temperature and strain rates are necessary to decide the optimum values of machine settings. This paper discusses the essential theoretical understanding of the process of metal extrusion, including the effects of die geometry, flow pattern and other variables with the help of the finite element program ABAQUS.
Keywords: ABAQUS; Extrusion; Modelling; Simulation